Genetic and genomic resources for Rubus breeding: a roadmap for the future. Issue 1 (15th October 2019) - Foster, Toshi M; Bassil, Nahla V; Dossett, Michael; Leigh Worthington, Margaret; Graham, Julie
Abstract: Rubus fruits are high-value crops that are sought after by consumers for their flavor, visual appeal, and health benefits. To meet this demand, production of red and black raspberries ( R. idaeus L. and R. occidentalis L.), blackberries ( R . subgenus Rubus ), and hybrids, such as Boysenberry and marionberry, is growing worldwide. Rubus breeding programmes are continually striving to improve flavor, texture, machine harvestability, and yield, provide pest and disease resistance, improve storage and processing properties, and optimize fruits and plants for different production and harvest systems. Breeders face numerous challenges, such as polyploidy, the lack of genetic diversity in many of the elite cultivars, and until recently, the relative shortage of genetic and genomic resources available for Rubus . This review will highlight the development of continually improving genetic maps, the identification of Quantitative Trait Loci (QTL)s controlling key traits, draft genomes for red and black raspberry, and efforts to improve gene models. The development of genetic maps and markers, the molecular characterization of wild species and germplasm, and high-throughput genotyping platforms will expedite breeding of improved cultivars. Fully sequenced genomes and accurate gene models facilitate identification of genes underlying traits of interest and enable gene editing technologies such as CRISPR/Cas9.